The EEG Oscillations and Psychology Propensities of Autonomous Sensory Meridian Response - Zhongliang Yu; Lili Li; Wenqing Zou; Muqing Lin; Jiayu Zheng; Zhiqing Wu; Zhizhong Wang (IEEE, 2023)
Autonomous sensory meridian response is believed as a perceptual phenomenon to specific sensory stimuli. To explore the underlying mechanism and emotional effect, the EEG under video and audio triggers of autonomous sensory meridian response was analyzed. The differential entropy and power spectral density by Burg method on $δ $ , $θ $ , $α $ , $β $ , $γ $ and high $γ $ frequencies were employed as quantitative features. The results indicate that the modulation of autonomous sensory meridian response on brain activities is broadband. Video trigger owns better performance of autonomous sensory meridian response than other triggers. Moreover, the results also reveal that autonomous sensory meridian response has a close relationship with neuroticism and its three sub-dimensions, anxiety, self-consciousness and vulnerability, with the scores of self-rating depression scale, but without emotions, happiness, sadness, or fear. This suggests that the responders of autonomous sensory meridian response may have the tendencies of neuroticism and depressive disorder.